Synthèse d'entretien avec le magistrat, juge des enfants - Tapsoba, Tatiana Nadine (Criminal justice institutions and the social trajectories of adolescents/youth in Burkina Faso: endogenous/local forms and patterns of punishment, 2021)
This interview took place on April 29, 2021 with a magistrate, a sitting judge who has held the position of children's judge. For 29 minutes, the participants discussed fault management mechanisms, forms of mediation, the population's perception of modern and traditional justice, and collaboration between these two bodies.
Keywords: Administration of Justice; Teenagers; Youth; Punishment; Judges; Juvenile courts